Awareness of Nigerian university students to environmental problems through information sources: case study of university of Ibadan (2004)
The study presents a descriptive analysis of university students' awareness of Nigeria's environmental problems using university of Ibdan (U.I) as a case study. Three hundred and eight (308) questionnaries were adminstered to these students. The findings indicated that U. I students' know quiet a lot about Nigeria's environmental problems. Respondents became aware of the environment through sources of information scuh as television, radio and newspapers which ranked highest from the findings. Students' opinion about environmental problems was positive, other findings revealed a strong willingness to participates in environmental practices. Awareness of environmental problems, information sources most consulted vis-a-vis specific environmental problems, students' opinion and their willingness to participate or show concern in environmental protection practices.